Lateral Displacement Behavior of IBS Precast Concrete Elements Reinforced with Dual System - Mohammed Yahya Mohammed Al-Fasih; Walid F. Edris; Samy Elbialy; Abdul Kadir Marsono; Abd Al-Kader A. Al Sayed (Salehan Institute of Higher Education, 2024)
Throughout history, the construction industry has been a significant contributor to construction waste, presenting an ongoing challenge in efficiently managing this waste to mitigate environmental pollution. The Industrialized Building System (IBS) stands out as a construction approach that utilizes prefabricated components made from various waste materials, implemented with machinery and formwork, leading to minimal waste production. The potential failure of IBS blockwork columns under lateral loads is a significant concern, and the deformation of these columns is crucial in assessing overall structural performance against lateral forces. This study focuses on examining the deformation and flexibility of components in IBS blockwork columns when subjected to lateral loads. Using Finite Element Modeling (FEM), a 1:5 scale prototype model of the dual-reinforced system IBS Block Work Column is analyzed. The IBS Block Work Column, comprising four prefabricated components assembled in the form of a crucifix plan to enhance lateral stability, is subjected to FEM analysis and experimental investigations. The study aims to explore the impact of four different shapes of reinforcement on deformation resistance. The findings suggest that employing a dual-reinforced system in the IBS Block Work Column enhances its resistance to lateral loads compared to a column with conventional reinforcement. Moreover, the assembled IBS Block Work Column exhibits greater stiffness than a single prefabricated component when subjected to lateral loads. Doi: 10.28991/CEJ-2024-010-01-020 Full Text: PDF